Pembekalan Ilmu Teknologi Informasi Dan AI (Artificial Intelligence) Sebagai Pendukung Persaingan Dunia Kerja Pada PKBM Bahrul Ulum - Rajin Nahampun; Norita Sinaga; Hari Setyawan (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Artificial Intelligence (AI) is increasingly transformative in various fields, including education and the world of work. For school students, AI can help personalize learning, provide recommendations for materials according to needs, and facilitate access to information through virtual assistants such as chatbots. In the world of work, AI increases efficiency by automating routine tasks, advanced data analysis, and predictive decision-making. However, challenges such as the digital divide and the need for skill enhancement need to be addressed so that the benefits of AI can be felt evenly. With the right understanding and utilization, AI has the potential to drive innovation and productivity in the digital era.